Proceedings of Coastal Dynamics 2009 : impacts of human activities on dynamic coastal processes ; Tokyo, Japan, 7-11 September 2009 - Mizuguchi, Masaru; Sato, Shinji (World Scientific Pub. Co., 2009)
Coastal Dynamics 2009 is the sixth conference in a sequence of technical speciality conferences bringing together field and laboratory experimentalists, theoreticians and modelers conducting research on the dynamics of the coastal systems. The multidisciplinary Coastal Dynamics 2009 will be of interest to coastal engineers, coastal geologists, oceanographers, and related scientists. It is also of relevance to coastal specialists and managers, and to those interested in preserving coastal zones. In Coastal Dynamics 2009, special emphasis will be placed on the impacts of human activity on dynamic coastal processes.